PKP-010 Impact of the RS1143634 polymorphism of interleukin 1β on infliximab exposure in crohn's disease and ulcerative colitis patients. (14th February 2016) - Santacana, E; Padullés, N; Padullés, A; Padró, A; Rodríguez-Alonso, L; Guardiola, J; Bas, J; Carreres, M; Colom, H
Abstract : Background: Due to the large inter-patient pharmacokinetic (PK) and pharmacodynamic (PD) variability of infliximab (IFX), clinical outcomes in patients with inflammatory bowel disease (IBD) exhibit substantial inter-subject variability. An association between the rs1143634 C allele in interleukin 1β (IL1β) and higher serum IL1β concentrations and a lower response to IFX in patients with Crohn's disease (CD) has been reported. Unravelling the impact of genetic polymorphisms on IFX exposure may help to refine therapy and improve clinical outcomes. Purpose: To confirm the effect of the rs1143634 single nucleotide polymorphism (SNP) of IL1β on IFX exposure and PK in CD and ulcerative colitis (UC) patients. Material and methods: Patients receiving IFX between July 2013 and December 2014 (n = 67) were genotyped for IL1 β polymorphisms. Associations between this SNP and pre-dose concentrations (Cmin, mg/L), dose adjusted Cmin (Cmin /D, mg/L/mg/month), area under the concentration-time curve (AUC, mg/h/L) and half-life (t1/2, days) at steady state were evaluated. Normalised by dose exposure parameters were statistically compared after log transformation. Pharmacokinetic and statistical analysis was performed using Nonmem 7.2 and SPSSv19, respectively. Results: 67 patients were included (56.7% CC, 34.3% CT and 9.0% TT). All patients who developed antibodies against IFX (ATI) were carriers C (15% of carriers C). 60% of carrier C patients had Cmin <3 mg/L vs 17% of TT patients. Univariate analysis demonstrated that median Cmin was statistically lower in carrier C patients than in TT patients (CC1.38; CT 2.78; TT 6.40, p = 0.013). Cmin /D (CC 0.04; CT 0.069; TT 0.153, p = 0.019) and AUC (CC 21771; CT 27825; TT 35875, p = 0.023) were also significantly lower in C carriers than in TT patients. t1/2 was significantly lower in CC patients than in CT or TT (CC 9.5 vs CT and TT 13) patients (p = 0.038). Analysis of negative ATI patients (n = 59) showed that median Cmin (2.05 vs 6.40; p = 0.018) and Cmin /D (0.051 vs 0.135, p = 0.036) were significantly lower in C carriers than in TT patients. 55% of carriers C had a Cmin <3 mg/L versus 17% of TT patients when ATI was negative. Conclusion: IL1β polymorphisms have a major influence on IFX exposure in IBD patients. The C allele was correlated with lower Cmin and Cmin /D. These results support the importance of IL1 β polymorphisms in IFX dose optimisation but further studies are needed. No conflict of interest.